Level Set Interactive Segmentation on Perforated Road Image using Region Based Active Countours Method with im’4 - Anike, Marleni (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2022)
An image will have a lot of interpretation meaning when compared to a text. However, there is nothing wrong with the original image being manipulated to achieve a certain goal. In digital image processing (PCD) there are image manipulation techniques without touching other objects, this is due to the difficulty of separating one object from another. One of the digital image segmentation techniques that is widely used for PCD and computer vision is level set. In this research, the strength of active contour will be tested which will segment area-based objects with potholes using Matlab R2016a. inner region taking into account im = 4 with imresize(mask, 8) iterations of 500.